Experimental investigation of double slope solar still integrated with PCM nanoadditives microencapsulated thermal energy storage - Lukmon Owolabi Afolabi, Lukmon Owolabi Afolabi; Christopher Chintua Enweremadu, Christopher Chintua Enweremadu; M.W. Kareem, M.W. Kareem; Adiat I. Arogundade, Adiat I. Arogundade; Kashif Irshad, Kashif Irshad; Saiful Islam, Saiful Islam; K.O. Oladosu, K.O. Oladosu; Abdulhafid M. Elfaghi, Abdulhafid M. Elfaghi; Djamal Hissein Didane, Djamal Hissein Didane (Elsevier, 2023)
Transparent covered slope solar stills are trending but characterised with low productivity, heat losses and high energy consumption, which are setbacks in practice. In this study, double slope solar still (DSSS) integrated with PCM-TES is presented. PCM was microencapsulated with epoxy resin composite using vacuum mould-filled techniques. Conventional DSSS and DSSS-TES data collected have been compared to establish the influence of TES on productivity. Daily average temperature of the glass cover, humid air, saline water, still basin absorbern and TES cavity for the DSSS-TES attained are 65.2 ◦C, 77.5 ◦C, 82.4 ◦C, 79.5 ◦C and 68.4 ◦C, respectively. DSSSTES has yielded higher production, with 7.5 Litres of potable water daily and extension in operation period by 3 h has been achieved. In addition, condensation and evaporation rates increased with increase in production by 105%. Integration of TES with the system has reduced the heat losses while leakages from PCM nanocomposite have been prevented by microencapsulated insulator. No trace of metals, bacteria and organic contaminants has been found in desalinated water. A payback period of 0.8 year has been recorded based on all-year-round operations. Findings are in good agreement with existing models. Moreover, sensorial characteristics obtained conform to WHO standards.